Caspian seawater desalination and whey concentration through forward osmosis (FO)-reverse osmosis (RO) and FO-FO-RO hybrid systems: Experimental and theoretical study. (October 2020) - Arjmandi, Mehrzad; Pourafshari Chenar, Mahdi; Altaee, Ali; Arjmandi, Abolfazl; Peyravi, Majid; Jahanshahi, Mohsen; Binaeian, Ehsan
Highlights: Hybrid systems are proposed for the concentration of whey and seawater desalination. Proposed systems are flexible and can generate different quality of freshwater. Concentrated whey in the FO1 unit is collected and sold as a valuable by-product. The impact of sales of concentrated whey on the cost of seawater desalination was studied. Desalination of seawater using the proposed hybrid systems will lead to profitability. Abstract: The current experimental and theoretical study proposes forward osmosis (FO)-reverse osmosis (RO) (FR*) and FO-FO-RO (FFR) hybrid systems to combine concentration of cheese whey and Caspian seawater desalination. The powerful TF-PMM was used as a FO membrane. The impact of sales of concentrated cheese whey on reducing Caspian seawater desalination costs was studied. The results showed that the TF-PMM has good potential for concentration of cheese whey with a water flux of about 12.62 L/m 2 h. In terms of permeate concentration (Cp ) and at low recovery rates (RR), the choice of FR* and FFR hybrid systems with 0.3 M NaCl as the draw solution (DS) should be the priority. At high RR, although the sensitivity of the type of system is reduced, the FR* system should not be used. The total power consumption (Est ) for the FR*-30 % and FR*-50 % systems are lower than that of a single RO unit. In FR* hybrid system by increasing the RR FO1, the power consumption of the FO unit and also the Est decreased. Also, in the FFR system, by increasing the concentration of the DS, while increasing the Est, the power consumption portion of the FO unit decreased. The existence of a valuable by-product in the proposed hybrid systems increases the allowable limit of the cost of required equipment and other operating costs to achieve profitability and reach the break-even point. In the meantime, the FR*-50 % system generates the most revenue, and also the quality of produced freshwater from the FFR-50 %–0.3 M system is the highest.